Identification and molecular characterisation of the necrosis and ethylene-inducing peptide 1-like proteins (NLPs) of Phytophthora cinnamomi - Van den Berg, Noelani (University of Pretoria, 2024)
Dissertation (MSc (Microbiology))--University of Pretoria, 2024.